2021
DOI: 10.1016/j.jpain.2021.03.150
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Brain Rhythms of Pain Using Transcranial Alternating Current Stimulation (tACS) - A Sham-Controlled Study in Healthy Human Participants

Abstract: Chronic pain is a major health care problem. A better mechanistic understanding and new treatment approaches are urgently needed. In the brain, pain has been associated with neural oscillations at alpha and gamma frequencies, which can be targeted using transcranial alternating current stimulation (tACS). Thus, we investigated the potential of tACS to modulate pain and painrelated autonomic activity in an experimental model of chronic pain in 29 healthy participants. In 6 recording sessions, participants compl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 65 publications
1
7
0
Order By: Relevance
“…Nevertheless, the changes in pain ratings did not differ between real α-tACS and sham stimulation conditions, indicating that α-tACS of SM1 did not overwhelmingly affect perceptual responses to suprathreshold painful stimuli. The lack of an α-tACS effect was consistent with a recent study reporting that α-tACS did not successfully modulate tonic experimental pain in healthy human participants 33 but was inconsistent with a study reporting the analgesic effects of α-tACS. 3 Nevertheless, differences in both tACS stimulation protocols and pain assessments should be noted when comparing results from this study and these previous studies.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Nevertheless, the changes in pain ratings did not differ between real α-tACS and sham stimulation conditions, indicating that α-tACS of SM1 did not overwhelmingly affect perceptual responses to suprathreshold painful stimuli. The lack of an α-tACS effect was consistent with a recent study reporting that α-tACS did not successfully modulate tonic experimental pain in healthy human participants 33 but was inconsistent with a study reporting the analgesic effects of α-tACS. 3 Nevertheless, differences in both tACS stimulation protocols and pain assessments should be noted when comparing results from this study and these previous studies.…”
Section: Discussionsupporting
confidence: 61%
“…Subjective pain perception in response to mechanical pain has been shown to attenuate during the application of somatosensory α-tACS, provided that the intensity of painful stimulation is uncertain. 3 By contrast, using an experimental model of tonic pain among healthy participants, May et al 33 reported that pain or pain-related autonomic activity was not significantly affected by somatosensory α-tACS. These 2 studies thus reported inconsistent results regarding how experimental pain perception was affected during the application of sensorimotor α-tACS (ie, “online effects” during stimulation).…”
Section: Introductionmentioning
confidence: 95%
“…The authors showed that alpha-tACS over bilateral sensorimotor cortices can reduce subject-reported pain when the intensity of an upcoming pain was uncertain. However, another study reported that alpha-tACS over bilateral sensorimotor cortices had no effect on experimental heat pain in healthy participants ( May et al, 2021 ). Clinical studies have investigated whether tACS modulates pain intensity in patients with chronic low back pain.…”
Section: Pain Control Targeting Abnormal Neural Oscillationsmentioning
confidence: 99%
“…Few tACS studies have adapted conditions other than somatosensory alpha oscillations to modulate pain. A recent study investigated whether gamma-tACS over bilateral prefrontal cortices modulates experimental heat pain ( May et al, 2021 ). Gamma oscillations in prefrontal areas encode pain intensity during experimental heat pain in healthy participants ( Schulz et al, 2015 ; Nickel et al, 2017 ) and are associated with ongoing back pain intensity ( May et al, 2019 ).…”
Section: Pain Control Targeting Abnormal Neural Oscillationsmentioning
confidence: 99%
“…Single-pulse TMS uses frequent sites of action, such as the primary motor cortex (M1) ( Savoie et al, 2020 ). tDCS and tACS cathode and anode positions: contralateral orbit (SO), primary sensory cortex (S1) ( Marlow et al, 2013 ; May et al, 2021 ). tRNS: cerebral cortex.…”
Section: Non-invasive Brain Stimulationmentioning
confidence: 99%